Government Valuers’ Perception on the Current Practice of Ecosystem Service Valuation in Malaysia - Wan Ab Rashid, Wan Nur Ayuni; Mohamad, Junainah; Kesumo Wardhani, Nurhastuty (Environment-Behaviour Proceedings Journal, 2024)
The study explores Malaysian valuers’ perception of ecosystem service valuation, focusing on the valuation approach, factors affecting ES value, and the provision of ES. The qualitative research design involved conducting interviews with experts in ecosystem service valuation to gain a deeper understanding of their perspectives and methods. This study offers crucial insights into the provision of valuation techniques for ES standards, serving as a guide for analyses and addressing current legal needs. This study will contribute to the existing body of knowledge and help practitioners who may use the study’s findings in practical settings.